A Comprehensive Review on the Beneficial Roles of Vitamin D in Skin Health as a Bio-Functional Ingredient in Nutricosmetic, Cosmeceutical, and Cosmetic Applications - Sofia Neonilli A. Papadopoulou; Elena A. Anastasiou; Theodora Adamantidi; Anna Ofrydopoulou; Sophia Letsiou; Alexandros Tsoupras (Applied Sciences)
Vitamin D, also called the “sunshine” vitamin, has gained great attention recently due to the observed high percentage of the worldwide population being deficient in this essential bioactive vitamin. Primarily, vitamin D was known for its important role in bone health. Nevertheless, recent research has shown its importance for the brain, heart, muscles, immune system, and skin health, due to its distinct bio-functionality in almost every tissue in the human body. Therefore, its deficiency has been highly correlated with multiple diseases, including skin and dermatologically associated ones. Moreover, different methodologies are applied to synthesize vitamin D, while the main vitamin D sources in human plasma levels and the factors that can cause adverse modifications are multiple. Further research upon vitamin D has exhibited its notable role against skin diseases, such as psoriasis, atopic dermatitis, vitiligo, acne, and rosacea. In this article, a critical review of the most relevant and significant information regarding the relationship between vitamin D and skin health is thoroughly conducted, while emphasis is given to its potential uses and benefits in several cosmetic applications. Current status, limitations, and future perspectives of such a potent bioactive are also extensively discussed.